2019
DOI: 10.1002/ar.24104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cilia Function in Rat Trachea Reconstructed Using Collagen Sponge Scaffold Seeded with Adipose Tissue‐Derived Stem Cells

Abstract: The tracheal lumen is essential for conducting air to the lung alveoli and for voice production. However, patients with severe tracheal stenosis and malignant tumors invading the trachea often require tracheal resection. Recently, various reported tissue engineering methods for tracheal reconstruction show that regeneration of ciliated epithelium in the reconstructed areas, as well as preservation of the luminal structure is possible. However, only few studies report on the mucociliary transport function in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Good biocompatibility and suitable biodegradability are prerequisite for a scaffold to be used in tracheal tissue engineering. Previous extensive studies have demonstrated that both PCL and collagen are biocompatible (Fu et al, 2015;Jia et al, 2020;Nakamura et al, 2020;Semitela et al, 2020), so we did not specifically test the biocompatibility of the composite using a cell proliferation assay (e.g., a CCK-8 kit) or cell viability assay (e.g., live-dead staining). Nevertheless, our results indicated that the biomimetic scaffold comprised of PCL and collagen support tracheal cartilage formation both in vitro and in vivo, which indirectly indicates that the 3D-printed PCL scaffold with embedded collagen exhibited satisfactory biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Good biocompatibility and suitable biodegradability are prerequisite for a scaffold to be used in tracheal tissue engineering. Previous extensive studies have demonstrated that both PCL and collagen are biocompatible (Fu et al, 2015;Jia et al, 2020;Nakamura et al, 2020;Semitela et al, 2020), so we did not specifically test the biocompatibility of the composite using a cell proliferation assay (e.g., a CCK-8 kit) or cell viability assay (e.g., live-dead staining). Nevertheless, our results indicated that the biomimetic scaffold comprised of PCL and collagen support tracheal cartilage formation both in vitro and in vivo, which indirectly indicates that the 3D-printed PCL scaffold with embedded collagen exhibited satisfactory biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of polymeric or metal mesh, collagen foam infused with fibrin gel, or non‐woven mesh mediated cell produced ECM have demonstrated promising results in vivo. [ 39,49,50 ] Departing from above designs, we fabricated cACM‐PGS construct. Owing to the similar elasticity and adequate stiffness, the firm anchorage between cACM and PGS pores was well maintained, which was critical to physical integrity and biological efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate laryngeal tissue engineering 85‐87,91,92,94,96,97,198‐306 …”
Section: Discussionmentioning
confidence: 99%